Atomistic manipulation of reversible oxidation and reduction in Ag with an electron beam. Issue 22 (23rd May 2019) - Sheng, Huaping; Zheng, He; Jia, Shuangfeng; Chan, Maria K. Y.; Rajh, Tijana; Wang, Jianbo; Wen, Jianguo
Abstract : Employing electrons for direct control of a nanoscale reaction is highly desirable since it enables fabrication of nanostructures with different properties at atomic resolution and with flexibility of dimensions and location. Abstract : Employing electrons for direct control of a nanoscale reaction is highly desirable since it enables fabrication of nanostructures with different properties at atomic resolution and with flexibility of dimensions and location. Here, applying in situ transmission electron microscopy, we show the reversible oxidation and reduction kinetics in Ag, well controlled by changing the dose rate of the electron beam. Aberration-corrected high-resolution transmission electron microscopy observation reveals that O atoms are preferably inserted and extracted along the 111 close-packed planes of Ag, leading to the nucleation and decomposition of nanoscale Ag2 O islands on the Ag substrate. By controlling the electron beam size and dose rate, we demonstrated the fabrication of an array of 3 nm Ag2 O nanodots in an Ag matrix. Our results open a new pathway to manipulate an atomistic reaction with an electron beam towards the precise fabrication of nanostructures for device applications.